Collaboration: Suggested Understandings. Issue 1 (March 2016) - Sundet, Rolf; Kim, Hesook Suzie; Ness, Ottar; Borg, Marit; Karlsson, Bengt; Biong, Stian
Abstract : In this article, we suggest that collaboration can be specified as a set of processes built around turntaking as the key process, with the processes of negotiation for common goals and putting differences to work as the two‐dimensional focus in collaborative practice. Turntaking connects therapeutic work to establishing relationships instead of focusing on motivational states. Common goals connect collaborative practice to the therapeutic alliance. Putting difference at the centre places collaborative practice within a dialogical perspective. We specify dialogue as the overarching perspective in this article, differentiating two different types of conversation within the concept: dialogical and dialectical as the processes of change. The dialectical leads to an agreement of goals and perspectives, while the dialogical is oriented to accepting differences in goals and perspectives. These are connected to two different paths to change within the present moment. The first describes a process of moving along in present moments that turn into now‐moments and are resolved in a moment of meeting. This could be seen as a description of dialectical conversations at a micro level. The second path to change occurs during quieter moments of therapeutic processes when participants are engaged in an intersubjective quest to negotiate the best fit between one's own intentions and those of the other. The therapist's skills to realise this include the use of service user feedback and following the lead of the family.